How special are early birds? Foreign language teaching and learning - McManus, Kevin (Language Science Press, 2022)
This volume honours the academic achievements and scholarship of Professor Florence Myles as a world-leading scholar in the fields of Second Language Acquisition (SLA) and French Linguistics, in particular for her work in corpus-based SLA and language policy in primary school education. In addition to reviews of the field (e.g., primary languages policy in the UK), the volume presents new research studies reflective of key theoretical and methodological issues in current SLA research, including theory-building, corpus-based investigations, studies of language development, as well as informing teacher professional development through research. Taken together, this edited book provides a wide-ranging and balanced account of Myles's work and speaks to her influence on SLA research and primary languages policy. We invite readers to learn more about the fascinating research presented here as inspired by Florence's dedication to field.